2012
DOI: 10.1590/s0102-695x2012005000099
|View full text |Cite
|
Sign up to set email alerts
|

Genus Mikania: chemical composition and phytotherapeutical activity

Abstract: Abstract:The genus Mikania ranks high in the list of best-selling natural products in the world. Its main distribution is in South America, but some species are found in Asia, North America and Africa. It is used for treating fever, rheumatism, colds and respiratory diseases, as well as snake bites and scorpion stings, due to its broad spectrum of action. There are approximately 430 species of this genus and only 12% have been studied, highlighting their chemical and pharmacological diversity. The main chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 107 publications
1
31
0
15
Order By: Relevance
“…These findings agree with experimentally identified anti-inflammatory and antihemorrhagic properties of the Mikania genus against myotoxic, neurotoxic, and inflammatory effects of snake venoms [2]. The above observations are further supported by the findings of other studies in rats that revealed 80% reduction in hemorrhage area following intradermal injection of Bothrops venom and Mikania extract administration [14], and reduction of inflammatory cells, edema, and hemorrhagic halo 3 h after administration of B. jararaca venom and Mikania leaf extract [10].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…These findings agree with experimentally identified anti-inflammatory and antihemorrhagic properties of the Mikania genus against myotoxic, neurotoxic, and inflammatory effects of snake venoms [2]. The above observations are further supported by the findings of other studies in rats that revealed 80% reduction in hemorrhage area following intradermal injection of Bothrops venom and Mikania extract administration [14], and reduction of inflammatory cells, edema, and hemorrhagic halo 3 h after administration of B. jararaca venom and Mikania leaf extract [10].…”
supporting
confidence: 90%
“…Many plants have been used to ameliorate the effects of snakebite [1]. Among them, Mikania glomerata commonly known as "guaco," a plant found in the Brazilian Atlantic Forest, possesses multiple medical properties associated with its constituent coumarins and their derivativesterpenes, phytosterols, and flavonoids [14]. It may ameliorate the consequences of ophidic envenomation, probably through inhibition of phospholipase A2, metalloproteases, and serine proteases, which are enzymes associated with envenomation symptoms [2,9].…”
Section: Introductionmentioning
confidence: 99%
“…Coumarin, an active component found in guaco, is considered to be one of the main constituents responsible for its medicinal activity. It is also used as a chemical marker for ensuring quality control of products derived from guaco (Anvisa, 2005a;Ferreira and Oliveira, 2010;Rufatto et al, 2012). Drying of guaco is a preferred method for conserving the activity of its active ingredients and extending the shelf life to ensure a continuous supply to the phytotherapeutic industry.…”
Section: Introductionmentioning
confidence: 99%
“…Its native distribution is in Central and South America. (2) Different parts of the plant Mikania micrantha are used to treat fever, jaundice, dysentery, rheumatism, colds, respiratory diseases and scorpion stings. (3) The leaves have been reported as good haemostatic agents.…”
mentioning
confidence: 99%